Enhancing student competencies through entrepreneurship and cultural collaboration: A community engagement approach - Syarifah Rahmawati; Iskandarsyah Madjid; Muhammad Azry Bin Khoiry; Muhammad Fatin Arafat; Nabila Salsa; Dinda Puspita Sari Hutahean; Indah Istara; Lisma Dewi Tarissa; Atina Harira M. Nasir; Muhammad Akhi; Dinda Fauziah Khairani Nasution; Jassha Belua Claresta; Afdhalul Rizki Muhammad; F. Fairuzzabadi (Journal of Community Service and Empowerment, 2023)
Entrepreneurship plays a crucial role in the global economy, Driving job creation, fostering innovation, and contributing to economic growth. However, Indonesia faces challenges in increasing the number of entrepreneurs and enhancing economic productivity. This article presents a case study on the Faculty of Economics and Business at Syiah Kuala University's community engagement activities aimed at developing students' entrepreneurial and cross-cultural competencies. The activities encompass experiential learning, mentorship, networking, and cultural collaboration, aligning with achieving Sustainable Development Goals (SDGs). Through experiential learning, students gain practical knowledge, problem-solving skills, and a global mindset, equipping them for entrepreneurship and business. Collaborative initiatives with international partners, such as Universiti Kebangsaan Malaysia, and interactions with Indonesian diaspora entrepreneurs in Singapore enhance students' cross-cultural competence. They learn to respect diversity, adapt to different cultural norms, and collaborate effectively across cultures. The activities also facilitate networking and collaboration, enabling students to establish connections with diaspora entrepreneurs and international peers. These connections can lead to future partnerships and collaborative efforts. The community engagement activities empower students with the skills, knowledge, and global perspective necessary to excel as entrepreneurs and positively impact the achievement of SDGs. The emphasis on economically viable, culturally sensitive, environmentally sustainable, and socially responsible entrepreneurship aligns with the broader goals of sustainable development, contributing to the development of sustainable entrepreneurship in higher education.